MANAJAMEN PEMBELAJARAN BAHASA ARAB DI MTS KALIWINING JEMBER - wahyuni, Sri; Avilya, Annisa; Kayyis, Kayyis; Mustofa, Bisri (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2026)
This study is motivated by the suboptimal integration of management functions in Arabic language learning, as well as the imbalance between students’ mastery of qawaʿid and their language skills. The aim of this study is to analyze the management of Arabic language learning at MTs Kaliwining Jember, encompassing planning, organizing, implementation, supervision, and development as an integrated system. This study employs a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing, with data validity ensured through source and technique triangulation. The findings indicate that learning management is carried out adaptively through flexible planning, functional organizing, varied implementation, and supervision based on layered evaluation. However, the integration among management functions has not yet operated optimally, resulting in an imbalance in learning outcomes. This study provides an empirical description of Arabic language learning management practices based on interconnected management functions and offers a reference for developing more integrated, effective, and sustainable learning strategies.